Surgical management strategies and clinical outcomes of cutaneous skeletal hypophosphatemia syndrome: a case series - Qiao, Yi; Dai, Jin; Zhuang, Ting; Liu, Yicong; Ren, Xiuzhi (Frontiers in Pediatrics, 2026)
ObjectiveTo evaluate the surgical treatment strategies and clinical efficacy in patients with cutaneous skeletal hypophosphatemia syndrome (CSHS).MethodsA retrospective analysis was conducted on three cases of CSHS treated at our institution. Clinical data included medical history, physical examination, laboratory tests (hypophosphatemia-related biomarkers and genetic testing), and imaging studies (x-ray and CT). Pre- and postoperative limb deformity correction and functional recovery were assessed.ResultsAll three patients presented with multiple skeletal deformities and cutaneous melanocytic nevi. Laboratory tests confirmed persistent hypophosphatemia, while imaging revealed widespread osseous abnormalities and long-bone bowing deformities. Following corrective osteotomy with internal fixation, significant improvement in mechanical alignment was achieved.ConclusionsSurgical intervention can effectively correct limb deformities, restore biomechanical alignment, and improve function in patients with CSHS. Hence, it represents a critical component of multidisciplinary management.